Numerical investigation of heat transfer by an impinging jet using alumina–water nanofluid. (18th October 2018) - Allauddin, U.; Mahrukh, M.; Rehman, N. U.; Haque, M. E.; Uddin, N.
Abstract: This article reports numerical investigations of turbulent flow field and heat transfer performance of water-alumina nanofluid jet impingement. The jet impinges over a flat, circular heated surface from a circular pipe of diameterD j t . The influence of jet Reynolds number (1, 200 ≤R e j t ≤ 40, 000), jet-outlet-to-target wall distance (2 ≤H / D j t ≤ 12.8), and particle volumetric concentration (0 ≤ φ  ≤ 10%) on the fluid flow and heat transfer are examined. The results of fluid flow and heat transfer are compared with the published experimental data. It is found that the heat transfer increases with increasing values of the particle volumetric concentration while the flow field and turbulent kinetic energy distribution remain unchanged with the inclusion of nanoparticles. About 28% enhancement in stagnation Nusselt number is observed at low values of nanoparticle volumetric concentration ( φ  = 0.1%) and in the Reynolds number range of 29, 000–40, 000. For jet-outlet-to-target wall spacingH / D j t values used in the current study, the local Nusselt number distributions vary according to Nu ∝R e j t 2 / 3 . Numerical simulations are performed using Reynolds-averaged Navier–Stokes method with the shear stress transport k-ω model in commercial CFD code ANSYS-CFX.